THE STUDY OF THE REACTION OF OXIDATION OF BENZYLIDENDIACETATE BY OZONE IN SOLUTION OF ACETATE ANHYDRIDE - Галстян, Андрій; Задворних, Іван; Косенко, Ольга (Technologies and Engineering, 2022)
Purpose. Study the kinetics of the oxidation reaction of benzylidendiacetate with ozone to determine the conditions under which the aldehyde will lose its tendency to further oxidation and become the target product. Methodоlogy. The oxidation kinetics of benzylidendiacetate were studied in a catalytic duck reactor. Mixing of gas and liquid phases in the reactor was achieved by shaking it at a speed of 8 s-1, which allowed to work in the kinetic region. The reaction kinetics were studied by measuring the concentration of ozone in the gas phase at the inlet and outlet of the reactor, which was recorded automatically using the spectrophotometric method in the absorption range of 254–290 nm. Identification of oxidation products and determination of their content in solution was carried out by gas chromatography on a chromatograph with a flame ionization detector. The analysis was performed on a 2 m long column filled with Chromaton N-AW carrier with SE-30 stationary phase applied to it in the amount of 5% by weight of the carrier. The temperature in the thermostat was regulated according to the program 373–473 К for 10 minutes. Gas speed – carrier (nitrogen 1.8); hydrogen 1.8; air 18 l/h. 4-nitrochlorobenzene was used as an internal standard. Findings. The kinetics and mechanism of liquid-phase oxidation of benzylidendiacetate by ozone have been studied. It is shown that the reaction proceeds in two directions: along the side chain with the formation of benzoic acid and the benzene ring with the subsequent destruction of the aromatic system. At temperatures up to 283 K, the reaction rate of ozone with benzyliden- diacetate is described by the second-order kinetic equation, according to which ozone is consumed by a non-chain ion-radical mechanism. At elevated temperatures, the chain depletion of ozone due to its participation in the reaction with the products of thermal decomposition of peroxides becomes noticeable. The stoichiometric coefficient for ozone in the reaction with benzylidendiacetate depends little on the ratio of reagents and temperature and in the range of 278–323 K is approximately 1.1. Originality. It has been shown that in the ozonation of toluene in the presence of sulfuric acid, acetic anhydride is not only a solvent, but also prevents further oxidation of benzaldehyde by ozone due to the rapid formation of ozone-resistant benzylidendiacetate. New kinetic regularities have been established, which supplement the existing ideas about the chemistry and technology of oxidation of arenes by ozone in the liquid phase. Practical value. The possibility of stopping the oxidation of toluene by ozone at the stage of benzaldehyde formation is shown. The obtained data can be the basis for the creation of a new low-temperature technology for the synthesis of benzaldehyde and its derivatives.